Evaluation of the the metabolic syndrome criteria and body composition in ambulatory children with Epilepsy in southern Iran: a case – control study - Inaloo, Soroor; Saki, Forough; Paktinat, Mohammad; Katibeh, Pegah; Nemati, Hamid; Ranjbar Omrani, Gholamhossein (Iranian Journal of Child Neurology, 2020)
Objectives: Previous studies in adults with epilepsy revealed a higher prevalence of metabolic syndrome, which resulted in cerebrovascular and cardiovascular events, however, there is insufficient data about body composition and metabolic syndrome in children, especially in Middle Eastern region. We aim to Investigate metabolic syndrome criteria and body composition in ambulatory children with Epilepsy in Southern Iran. Material and Methods: 90 children aged 11.4 ± 3.2 years with epilepsy and their age- gender-matched controls were included in this study. Anthropometric data, lipid profile, blood sugar and blood pressure were checked. Body composition was evaluated using Hologic system dual – energy X-ray absorptiometry. Results: Prevalence of metabolic syndrome in patients (6.7%) was more than the controls (1.1%) (p-value = 0.043). Patients’ fat mass index was more than the controls (P = 0.012), and lean mass+ Bone Mineral Content (BMC) index lower than the controls (P = 0.017). Serum triglycerides in patients using carbamazepine was higher than the others (P = 0.019, Beta = 0.379). Blood pressure was higher in patients using carbamazepine (p = 0.016, Beta = -0.26). Fat mass index was higher in patients using sodium valproate (p = 0.031, Beta = 0.238). Conclusion: Our study revealed that children with epilepsy are more prone to metabolic syndrome and higher body fat mass. Therefore, early diagnosis and prevention of metabolic syndrome criteria in patients with epilepsy, performing regular exercise and having a healthy diet should be encouraged in these children.